A new history of Japanese cinema : a century of narrative film - Standish, Isolde (Continuum, 2005)
In A New History of Japanese Cinema Isolde Standish focuses on the historical development of Japanese film. She details an industry and an art form shaped by the competing and merging forces of traditional culture and of economic and technological innovation. Adopting a thematic, exploratory approach, Standish links the concept of Japanese cinema as a system of communication with some of the central discourses of the twentieth century: modernism, nationalism, humanism, resistance, and gender.